Англи хэлний үйлт нэрийг монгол хэлнээ илэрхийлэх нь: Expression of English Participles in Mongolian - М., Алтанцэцэг; Ц., Бүүвэйбаатар (Mongolian Studies, 2023)
In this article we have made an analysis of English Participles in Mongolian language and explain why it is important and useful in English language teaching. We tried to determine its form, structure, some specific features and of its role and meaning both in English and Mongolian languages. There are general and similar things between English and Mongolian Participle by comparing their formation. Besides this, there are the things with differences, depending on the structure of two languages and its features . In this article we have noticed the ability to use the language dependent on the ability to bring grammar and vocabulary together. So it must make sense sometimes to teach words which are grammatically linked.